Titin M-line insertion sequence 7 is required for proper cardiac function in mice - Biquand, Ariane; Spinozzi, Simone; Tonino, Paola; Cosette, Jérémie; Strom, Joshua; Elbeck, Zaher; Knöll, Ralph; Granzier, Henk; Lostal, William; Richard, Isabelle (Journal of cell science, 2021)
Titin is a giant sarcomeric protein that is involved in a large number of functions, with a primary role in skeletal and cardiac sarcomere organization and stiffness. The titin gene (TTN) is subject to various alternative splicing events, but in the region that is present at the M-line, the only exon that can be spliced out is Mex5, which encodes for the insertion sequence 7 (is7). Interestingly, in the heart, the majority of titin isoforms are Mex5+, suggesting a cardiac role for is7. Here, we performed comprehensive functional, histological, transcriptomic, microscopic and molecular analyses of a mouse model lacking the Ttn Mex5 exon (ΔMex5), and revealed that the absence of the is7 is causative for dilated cardiomyopathy. ΔMex5 mice showed altered cardiac function accompanied by increased fibrosis and ultrastructural alterations. Abnormal expression of excitation–contraction coupling proteins was also observed. The results reported here confirm the importance of the C-terminal region of titin in cardiac function and are the first to suggest a possible relationship between the is7 and excitation–contraction coupling. Finally, these findings give important insights for the identification of new targets in the treatment of titinopathies.